Knowledge Management, Library and Literature - Senapati, S. K. (Journal of Information and Knowledge, 2006)
The paper provides an overview of knowledge, knowledge management and libraries. Discusses different aspects of knowledge management in a library. Clarifies the basics of knowledge managers and role of librarians. Enumerates the seminars and conferences held during last five years at national and international level on knowledge management to enhance the literature output.